2015
DOI: 10.3390/proteomes3030298
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Label-Free Mass Spectrometric Analysis of Dystrophin Isoform Dp427 and the Myofibrosis Marker Collagen in Crude Extracts from mdx-4cv Skeletal Muscles

Abstract: The full-length dystrophin protein isoform of 427 kDa (Dp427), the absence of which represents the principal abnormality in X-linked muscular dystrophy, is difficult to identify and characterize by routine proteomic screening approaches of crude tissue extracts. This is probably related to its large molecular size, its close association with the sarcolemmal membrane, and its existence within a heterogeneous glycoprotein complex. Here, we used a careful extraction procedure to isolate the total protein repertoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 109 publications
4
41
0
Order By: Relevance
“…Numerous proteoglycans such as biglycan (Bgn), decorin (Dcn), lumican (Lum), osteopontin (Spp1), tenascin C (Tnc), tenascin X (Tnxb), versican (Vcan), vinculin (Vcl), and vimentin (Vim) were upregulated at the transcript or protein level ( Figure 3D). These observations are consistent with previous findings in 3 month old mdx and 6 month old mdx 4cv animals, which are thought to have a more severe muscle phenotype from the original strain of mdx mice (32,33).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Numerous proteoglycans such as biglycan (Bgn), decorin (Dcn), lumican (Lum), osteopontin (Spp1), tenascin C (Tnc), tenascin X (Tnxb), versican (Vcan), vinculin (Vcl), and vimentin (Vim) were upregulated at the transcript or protein level ( Figure 3D). These observations are consistent with previous findings in 3 month old mdx and 6 month old mdx 4cv animals, which are thought to have a more severe muscle phenotype from the original strain of mdx mice (32,33).…”
Section: Resultssupporting
confidence: 93%
“…However, type Iα1 and type Iα2 collagen had a lower abundance in mdx/mTR muscles, while type VIα1 collagen protein was not different despite having an elevation in transcript ( Figure 3D). In 6 month old mdx 4cv animals, an elevation in type Iα1 and type VIα1 collagen protein was observed (33). It is possible that the differences between these results in collagen changes are due to an earlier degenerative stage of the mdx/mTR mice, prior to the onset of more severe fibrosis.…”
Section: Resultsmentioning
confidence: 96%
“…The trifunctional enzyme complex of the inner mitochondrial membrane system is an important component that mediates fatty acid utilization and altered enzymatic functionality has severe pathophysiological consequences . A previous survey of crude microsomal membranes by MS‐based proteomics has revealed elevated levels of this metabolic enzyme in dystrophin‐deficient skeletal muscle tissue . The 2‐oxoglutarate dehydrogenase complex is a multi‐enzyme assembly of the mitochondrial matrix that catalyses the overall conversion of 2‐oxoglutarate to succinyl‐CoA and CO 2 as a crucial part of the citric acid cycle in skeletal muscle .…”
Section: Discussionmentioning
confidence: 99%
“…Label free proteomic approaches allowed studying molecular basis of muscle dystrophy [4][5][6] . A few recent studies have demonstrated that the filter aided sample preparation (FASP) 7 and multienzyme digestion FASP (MED-FASP) 8 methods facilitate proteomic analysis of muscles enabling creation of quantitative picture of the cellular organization and providing titers of individual proteins [9][10][11] Recently, we have described a simple analytical and computational approach to estimate titers of enzymes of basic metabolic pathways and proteins of the contractile machinery in skeletal muscles of mouse 10 .…”
Section: Introductionmentioning
confidence: 99%